The legal perspective of the protection of women and children in Edo State (2017)
Protection of women and children has been the international challenge that the world has been battling to surmount. As a result, gender issues have become a recurrent theme in local, national and international gatherings. In spite of the efforts that have been dissipated so far to combat this menace, particularly at the global level, the challenge still remains. This is due to the fact that most gender issues are deeply rooted in the cultures of the people and that should demand for a grass root approach to address them. In light of that recognition, this article examines how the law of Edo State protects women and children from unfair customs and discriminatory practices. It discusses the cultures of Edo State people, their peculiarity and how those cultures violate the rights of women and children. Thereafter, different mechanisms adopted to protect them are also discussed and recommendations are made on how the challenge can be addressed.